Molecular Mechanisms and Therapeutic Potential of Soy Isoflavones in Breast Cancer: A Narrative review - Rusnita, Dewi; Nurhajjah, Siti; Syah, Nur Afrainin (Jurnal Kesehatan - STIKes Prima Nusantara, 2026)
Breast cancer remains a multifaceted disease requiring deeper understanding of dietary interventions. Soy isoflavones represent a promising area of investigation. Despite extensive research, a synthesis of insights from laboratory, animal, and human research to elucidate mechanisms by which soy isoflavones could be used for preventing and treating breast cancer remains lacking. This review analyses recent findings laboratory, animal and human research to clarify molecular mechanisms of soy isoflavones in breast cancer prevention and treatment. Soy isoflavones, particularly genistein and daidzein, influence cell proliferation, cell cycle regulation, apoptosis induction, epigenetic modifications, cell signalling pathways, angiogenesis, and metastasis in breast cancer models. These compounds modulate expression of crucial genes and proteins participate in these processes, such as p21, Bax, Bcl-2, BRCA1, and BRCA2, and disrupt essential cancer signalling pathways. Soy isoflavones impact breast cancer cell metabolism, particularly glucose, lipid, and nucleotide metabolism, through effects on the pentose phosphate pathway. These compounds demonstrate immunomodulatory properties, influencing immune cell recruitment and signalling in the breast cancer microenvironment. While soy isoflavone effects vary based on dose, timing of exposure, and tumour subtype, evidence suggests their potential as chemopreventive agents, warranting further clinical investigation.